2018
DOI: 10.2147/cbf.s160340
|View full text |Cite
|
Sign up to set email alerts
|

Urine volatile organic compounds composition in mice bearing breast and melanoma tumors: effect of low-protein diet

Abstract: Background: Volatile organic compounds (VOCs) in urine may provide information about biomarkers of tumors in their early stages and about tumor growth. Methods: This study demonstrates that the effect of low protein diet on the pattern of VOCs in the urine of healthy and cancer bearing mice is significant. Results: Pentanal, found in nine out of the ten breast cancer-bearing mice on a high protein (HP) diet, was not found in any of the cancer bearing mice under a low protein (LP) diet, even after tumor develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…For example, in a study conducted with mice carrying breast cancer, some VOCs were found in the urine of mice on a high protein diet and not in the urine of any mice on a low protein diet [ 30 ]. Therefore, the presence of some VOCs in the MF of only one breeding/age group could be attributed to either the type of protein/s received or the difference in supplementation between the groups (e.g., 3-pentanone), whereas the absence/presence of some VOCs collected from the same cheetah at different times/days could be explained by the endocrine status of the cheetah at the time of collection [ 26 , 30 ]. For example, 2-ethenyl-6-methyl-pyrazine and decanal were identified only in one of the two samples collected from the same animal on different days (15th and 20th of March 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a study conducted with mice carrying breast cancer, some VOCs were found in the urine of mice on a high protein diet and not in the urine of any mice on a low protein diet [ 30 ]. Therefore, the presence of some VOCs in the MF of only one breeding/age group could be attributed to either the type of protein/s received or the difference in supplementation between the groups (e.g., 3-pentanone), whereas the absence/presence of some VOCs collected from the same cheetah at different times/days could be explained by the endocrine status of the cheetah at the time of collection [ 26 , 30 ]. For example, 2-ethenyl-6-methyl-pyrazine and decanal were identified only in one of the two samples collected from the same animal on different days (15th and 20th of March 2020).…”
Section: Resultsmentioning
confidence: 99%
“…However, since in this study, the age groups (younger and older) corresponded to the non-breeding and breeding group, respectively, it was not possible to distinguish if the differences in RC of the commonly identified VOCs observed from the older B males were related to their exposure to the females or to the physiological differences due to the age, such as sperm quality, or if the two are somehow related. Furthermore, the differences in the diet between the two groups may have affected the absence/presence of certain VOCs [ 30 ]. Other limitations, such as the limited sample size, could have affected the results as well.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fernandez Del Rio et (2017 & 2020) found that restoring liver function with a liver transplant reduces compound 9 levels in the breath and restores them to normal [14,33], although one study has stated that compound 9 level is elevated in the breath of cirrhotic patients due to CYP450 enzyme inactivity, as seen in Fig 7 . In this study, the results support the above theory that variations in CYP450 enzyme activity between healthy and cirrhotic individuals increased the level of compound 9 in the exhaled breath of cirrhotic patients. Certain studies [34] examined VOCs in the breath of patients with liver disease, and certain VOCs have been proposed as biomarkers for cirrhosis. Sulfur compounds are associated with liver disease and are responsible for the distinct odor of patients' breath known as Foetor Hepaticus.…”
Section: Plos Onementioning
confidence: 99%
“…Investigators have explored the panoply of prospective biomarkers, numerous of which would designate improper immune function as well as signs of autoimmunity, and some liver biomarkers are used for detecting the problems related to the liver (Fig. 7) [50,51].…”
Section: Recent Developmentsmentioning
confidence: 99%